The effectiveness mechanisms to reduce poverty rate and improving the standard of living – A case study of South Darfur state – - Adam, Sofian Abuelbacher; Osman, Hassan Ali; Alfadl, Asim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the effectiveness of the mechanisms used to reduce the Poverty rate and improving the standard of living in the area of the study. Descriptive Analytical method was used. The primary data has been collected by using a questionnaire as the main tool of data collection from poor who have given projects during the period of study. A random sample consists of sixty persons was selected. The study concluded to the many results, the most important one is the effective role of the tools in reducing poverty in the state has been realized due to the analysis proved by Chi-Square indication of 0.05 reflected that there is an inverse relationship having a positive impact statistically between the projects of Zakat Chamber, microfinance and voluntary organizations and bettering livelihoods level in the state. The study recommended that the necessity for Zakat Chamber, microfinance and voluntary organizations to supervise and follow up the projects that given to poor in order to sustain their successfulness.
Keywords: Zakat office; microfinance; voluntary organizations; reducing poverty